Subcutaneous Mercury Injection by a Child: A Histopathology Case Report - Sukheeja, Deepti (Medknow Publications & Media Pvt Ltd, 2014)
Intentional subcutaneous injection of mercury by mentally healthy children is rare. Usually, it is seen as a part of suicidal attempt in severely depressed patients or by athletes to enhance their performance. We report a case of a 15-year-old child, inspired by a movie, who deliberately self-injected mercury subcutaneously into his forearm that led to the formation of a non-healing ulcer. Histopathology of the biopsy confirmed the diagnosis. A surgical procedure was thereby performed to treat the ulcer and reduce the blood and urinary levels of mercury. However, the patient did not develop clinical signs of chronic poisoning, proving that subcutaneous mercury injection has a low risk of systemic toxicity, and that histopathology plays an important role in diagnosis.